An evaluation for spirit of place focused preservation approaches in historic environments - Guner, Remziye; Polat, Elvan Ebru Omay (YILDIZ TECHNICAL UNIV, FAC ARCHITECTURE, 2023)
The starting point of this article is the thought that the effort to protect the meanings created by the collective experiences is lacking, even though the physical integrity of a historical environment is tried to be conserved in the preservation activities that have been done or are being done from the past to the present. However, historical environments have existed as a product of collective experiences as well as being a physical accumulation, and they carry these experiences as a meaning. While trying to define this meaning, the concept of spirit of place (genius loci), which emerged as a reflection of the existential debates of space, and has been continuing since the end of the 19th century, among the philosophical theorists in the middle of the 20th century, was encountered and the origin, adventure and existence of this concept in the field of preservation were researched. As a result, it was concluded that the meaning deemed necessary to be included in preservation processes is a component that will be identified and documented with the title of spirit of place. To do this, a method needs to be determined and the research process needs to be carried out more systematically. This paper, which seeks a method for defining the spirit of place in historical environments, aims to shed light on a holistic approach in which the concern of preserving the spirit of place is included in the historical environment preservation process.
Keywords: Genius loci; meaning of place; preservation of historical environment; sense of place; spirit of place; Architecture